Nanoscale control of molecular self-assembly induced by plasmonic hot-electron dynamics - Simoncelli,S; Li,Y; Cortés,E; Maier,SA (ACS Nano, 2018)
Self-assembly processes allow designing and creating complex nanostructures using molecules as building blocks and surfaces as scaffolds. This autonomous driven construction is possible due to a complex thermodynamic balance of molecule-surface interactions. As such, nanoscale guidance and control over this process is hard to achieve. Here we use the highly localized light-to-chemical-energy conversion of plasmonic materials to spatially cleave Au-S bonds on predetermined locations within a single nanoparticle, enabling a high degree of control over this archetypal system for molecular self-assembly. Our method offers nanoscale precision and high-throughput light-induced tailoring of the surface chemistry of individual and packed nanosized metallic structures by simply varying wavelength and polarization of the incident light. Assisted by single-molecule super-resolution fluorescence microscopy, we image, quantify, and shed light onto the plasmon-induced desorption mechanism. Our results point toward localized distribution of hot electrons, contrary to uniformly distributed lattice heating, as the mechanism inducing Au-S bond breaking. We demonstrate that plasmon-induced photodesorption enables subdiffraction and even subparticle multiplexing. Finally, we explore possible routes to further exploit these concepts for the selective positioning of nanomaterials and the sorting and purification of colloidal nanoparticles.